Penentuan Margin Planning Target Volume (PTV) Radioterapi dengan Teknik IMRT Kasus Kanker Nasofaring - Sitti Fathul Jannah; Dewang, Syamsir; Male, Satrial (JRI (Jurnal Radiografer Indonesia), 2024)
Background: This research was conducted to determine PTV margins from the results of geometry verification using 3 calculation formulas for nasopharyngeal cancer cases with Intensity Modulated Radiation Therapy (IMRT) techniques and recommend the most suitable calculation method for determining PTV margins. Verification is important to determine whether there is a shift in radiotherapy planning. Geometry errors or shifts were analyzed to obtain PTV margin values and reduce setup errors including systematic and random errors. Methods: This type of research is quantitative research with interactive methods, interviews, documentation, and data collection of patient verification results. Geometry verification was carried out 3 times in the first fraction, 10th fraction, and 20th fraction using Electronic Portal Imaging Device (EPID) for nasopharyngeal cancer (KNF) cases at Radiotherapy Installation Pelamonia Hospital Makassar. Results: The results showed that the random error was greater than the systematic error, indicating that it is more difficult to correct the random error due to its changing value. This occurs due to the movement of the organ around the target. Conclusions: The PTV margin values in each formula were found to be 10.31 cm x-axis; 8.47 cm y-axis; and 60.34 cm z-axis using the Van Herk formula. The PTV margin using Stroom formula was 8.79 cm x axis; 7.15 cm y-axis; and 51.47 cm z-axis. The PTV margin using the ICRU 62 formula was 4.90cm x axis; 3.75cm y-axis; and 28.92cm z-axis. Van Herk's formula PTV margin is recommended based on the lowest percentage shift that lies outside the PTV margin.